Perspective on Dentoalveolar Manifestations Resulting From PHOSPHO1 Loss-of-Function: A Form of Pseudohypophosphatasia? - Mohamed, Fatma F.; Chavez, Michael B.; Amadeu de Oliveira, Flavia; Narisawa, Sonoko; Farquharson, Colin; Millán, José Luis; Foster, Brian L. (Frontiers in Dental Medicine, 2022)
Mineralization of the skeleton occurs by a number of physicochemical and biochemical processes and mechanisms that facilitate the deposition of hydroxyapatite in specific areas of the extracellular matrix. Two key phosphatases, Phosphatase, Orphan 1 (PHOSPHO1) and tissue-nonspecific alkaline phosphatase (TNAP), play complementary roles in the mineralization process. The actions of PHOSPHO1 on phosphocholine and phosphoethanolamine in matrix vesicles (MVs) produce inorganic phosphate (Pi) for initiation of HA mineral formation within MVs. TNAP hydrolyzes adenosine triphosphate (ATP) and the mineralization inhibitor, inorganic pyrophosphate (PPi), to generate Pi that is incorporated into MVs. Genetic mutations in the ALPL gene encoding TNAP lead to hypophosphatasia (HPP), characterized by low circulating TNAP levels (ALP), rickets in children and/or osteomalacia in adults, and a spectrum of dentoalveolar defects, the most prevalent being lack of acellular cementum leading to premature tooth loss. Given that the skeletal manifestations of genetic ablation of the Phospho1 gene in mice resemble many of the manifestations of HPP, we propose that Phospho1 gene mutations may underlie some cases of “pseudo-HPP” where ALP may be normal to subnormal, but ALPL mutation(s) have not been identified. The goal of this perspective article is to compare and contrast loss-of-function effects of TNAP and PHOSPHO1 on the dentoalveolar complex in order to predict the likely dental phenotype in humans that may result from PHOSPHO1 mutations. Potential cases of pseudo-HPP associated with PHOSPHO1 mutations may resist diagnosis, and the dental manifestations could be a key criterion for consideration.